Salicylaldehyde-functionalized block copolymer nano-objects: one-pot synthesis via polymerization-induced self-assembly and their simultaneous cross-linking and fluorescence modification. Issue 29 (30th June 2016) - Huang, Jianbing; Zhu, Hanjun; Liang, Hui; Lu, Jiang
Abstract : Salicylaldehyde-functionalized nano-objects are prepared via RAFT-mediated polymerization-induced self-assembly. Their simultaneous stabilization and fluorescence modification can be achieved by one-step reaction. Abstract : Salicylaldehyde-functionalized diblock copolymer nano-objects were synthesized by polymerization induced self-assembly (PISA) via RAFT dispersion polymerization of a newly designed core-forming monomer, 3-formyl-4-hydroxybenzyl methacrylate (FHMA), using the poly(2-hydroxypropyl methacrylate) (PHPMA) macromolecular chain transfer agent as a steric stabilizer in methanol at 65 °C. A range of PHPMA- b -PFHMA block copolymer morphologies including spheres, worms and vesicles could be accessed by adjusting the degree of polymerization of the core forming PFHMA block. Since the salicylaldehyde groups of core-forming PFHMA blocks could react with hydrazine in a 2 : 1 stoichiometry to form salicylaldazines with aggregation-induced emission, one-step post-modification of the PISA nano-objects using hydrazine enabled their inherent nanostructures to be stabilized via covalent cross-linking and simultaneously conferred luminescent features on the resulting stabilized nanoparticles. Solid nano-objects, obtained easily via precipitation into diethyl ether, could be re-dispersed well in methanol and THF. The nano-objects could also be re-dispersed in water to form colloidal dispersions at a low concentration (≤1% w/w). Thanks to the stability imparted by the cross-linking, the morphologies of the preformed PISA nano-objects remained intact even after re-dispersing these cross-linked nano-objects in THF (a good solvent for both blocks). The stabilized nano-objects displayed strong orange fluorescence in water, organic solvents or solid state. This work opens the possibility for simultaneous functionalization and stabilization of PISA-generated block copolymer nano-objects.